PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN PERPAJAKAN, RELIGIUSITAS DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS PADA WAJIB PAJAK ORANG PRIBADI YANG TERDAFTAR DI KPP PRATAMA KEBUMEN) - Atika, Desi; Handayani, Henni Rahayu (Jurnal Nusa Akuntansi, 2024)
This study aims to determine the effect of taxpayer awareness, tax knowledge, religiosity, and tax socialization on individual taxpayer compliance. The sample in this study consists of 100 respondents. The respondents are individual taxpayers registered at the KPP Pratama Kebumen. The data in this study were analyzed using SPSS version 25. The results of the study indicate that there is a partial and significant influence of taxpayer awareness on individual taxpayer compliance. Tax knowledge has a partial and significant effect on individual taxpayer compliance, religiosity has a partial and significant effect on individual taxpayer compliance, and tax socialization affects individual taxpayer compliance. Simultaneously, there is an influence of taxpayer awareness, tax knowledge, religiosity, and tax socialization on individual taxpayer compliance at KPP Pratama Kebumen.